Effect of temperature on the rheological behavior of zapote pulp (Calocarpum sapota Merr) - Ricardo David Andrade Pizarro; Ramiro Torres Gallo; Everaldo Joaquín Montes Montes; Omar Andrés Pérez Sierra; Cindy Elena Bustamante Vargas; Bettyna Beatriz Mora Vargas (Revista Técnica de la Facultad de Ingeniería, 2012)
The effect of temperature on the rheological behavior of whole zapote pulp (Calocarpum sapota Merr) was determined, with temperatures ranging from 10°C to 65°C. For the obtaining of the zapotes pulp, they were processed in the plant pilot fruits and vegetables section of the University of Córdoba, to this pulp were made rheological analyses to different temperatures by means of the Brookfield viscometer model Dv-II + Pro. The apparent viscosity data adjusted to properly the Power Law model (R2 Â³ 0.9958) with consistency index of 637 to 3800 Pa.sn and flow behavior index of 0,027 to 0,133, presenting a pseudoplastic behavior. The consistency index diminished with the temperature and flow behavior index increased, which indicates that the zapote pulp loses pseudoplasticity and becomes less viscous when the temperature is increased.